The Effect of Price, Product Quality, and Location on Consumer Buying Interest at Pak Nu's Meatball Stall in Banda Aceh - T. Andi Roza; Gunawan; Syarifah Mauli Masyithah; Musnida; Vilzati Juned (International Journal of Seocology, 2022)
This study aims to analyze the effect of price, product quality, and location on consumer buying interest at Pak Nu's meatball stall in Banda Aceh. The problem that arises is whether price, product quality, and location affect consumer buying interest? Thus, this study aims to determine the effect of price, product quality, and location on consumer buying interest simultaneously or partially. The method used is Multiple Linear Regression Analysis. The results obtained are expected to provide an explanation of the relationship between the independent variables on the dependent variable. The research sample selected according to the criteria amounted to 100 samples. The sampling technique is purposive and the data used is the source of the data used, namely the primary data obtained from the results of filling out the questionnaire. The results of this quantitative study indicate that the price partially has a significant effect on consumer buying interest at Pak Nu's meatball stall in Banda Aceh where the value of tCount greater than ttable that is tCount (2,203) > ttable (1,984). Product quality partially affects buying interest at Pak Nu's meatball stall in Banda Aceh where the value of tCount greater than ttable That is tCount (2,600) > ttable (1,984). Location partially has no effect on buying interest at Pak Nu's meatball stall in Banda Aceh where the value of tCount greater than ttable that is tcount (3,662) < ttable (1,984) price, product quality and location simultaneously affect buying interest at Pak Nu's meatball stall in Banda Aceh where the value of Fcount greater than Ftable that is Fcount (7,999) > Ftable (2,70).